Britishness and identity assimilation among the UK's minority and majority ethnic groups - Alita Nandi; Lucinda Platt (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Public and academic debate has revealed concern with the extent and implications of national identification among minority groups in Western societies. In this paper we present new analysis of Understanding Society that expands the limited evidence on minority identification. Drawing on Berrys acculturation framework, we explore patterns of dual minority and majority identification among the UKs minority ethnic groups. We find that minorities tend to hold strong British identities; but that that there are variations in identity acculturation across minority groups and by generation. We also show that there is substantial heterogeneity in the identities of the White majority population.
Keywords: J15; Z12; 330; identity; UK; British; minorities; second generation